Transformation products of pharmaceuticals in surface waters and wastewater formed during photolysis and advanced oxidation processes - degradation, elucidation of byproducts and assessment of their biological potency - Fatta-Kassinos, Despo; Vasquez Christodoulou, Marlen; Kümmerer, Klaus (My University, 2011)
The significance of transformation products of pharmaceuticals resulting from the parent compounds during natural and technical photolytic processes and advanced oxidation processes has only recently started to attract the interest of the scientific community. Even though relevant studies have now started to produce important knowledge, still many gaps exist that hinder the in-depth and broad understanding of the extent of the potential problems stemming from the presence of such compounds in the environment and the applicability of such techniques for wastewater and potable water treatment. The great diversity of pharmaceutical compounds, the variety of processes and conditions applied by the various research groups active in the field, and the endless list of potential biological endpoints that could potentially be explored, coupled with the limitations related to the analytical capabilities presently available, are some of the crucial parameters that characterize this challenging research direction. This review paper tries to highlight some of the most relevant studies performed so far and to summarize the parameters that prevent scientists from reaching comprehensive conclusions in relation to the formation, fate, and effects of transformation products of pharmaceutical compounds during photo-driven and advanced oxidation processes.
Keywords: Pharmaceutical; Transformation product; Photolysis; Advanced oxidation process; Antibiotic activity; (Eco)toxicity